Anterior Lumbar Interbody Fusion in Elderly Patients: Peri- and Postoperative Complications and Clinical Outcome - Jesse, Christopher M.; Mayer, Lea; Häni, Levin; Goldberg, Johannes; Raabe, Andreas; Schwarzenbach, Othmar; Schär, Ralph T. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Anterior lumbar interbody fusion (ALIF) is an effective surgical technique for treating various lumbar pathologies, but its use in elderly patients is controversial. Data concerning complications and effectiveness are sparse. We investigated peri- and postoperative complications, radiographic parameters, and clinical outcome in elderly patients.Methods Patients ≥65 years who underwent ALIF between January 2008 and August 2020 were included in the study. All surgeries were performed through a retroperitoneal approach. Clinical and surgical data as well as radiologic parameters were collected prospectively and analyzed retrospectively.Results A total of 39 patients were included; the mean age was 72.6 (±6.3) years (range: 65–90 years); and the mean American Society of Anesthesiologists (ASA) risk classification was 2.3 (±0.6). A laceration of the left common iliac vein was the only major complication recorded (2.6%). Minor complications occurred in 20.5% of patients. Fusion rate was 90.9%. Reoperation rate at the index level was 12.8 and 7.7% in adjacent segments. The multidimensional Core Outcome Measures Index (COMI) improved from 7.4 (±1.4) to 3.9 (±2.7) after 1 year and to 3.3 (±2.6) after 2 years. Oswestry disability index (ODI) improved from 41.2 (±13.7) to 20.9 (±14.9) after 1 year and to 21.5 (±18.8) after 2 years. Improvements of at least the minimal clinically important change score of 2.2 and 12.9 points in the ODI and COMI after 2 years were noted in 75 and 56.3% of the patients, respectively.Conclusion With careful patient selection, ALIF is safe and effective in elderly patients.
Keywords: ALIF; anterior lumbar interbody fusion; lumbar fusion; spine surgery in elderly